EINSTEIN’S WORK IN THE FIELD OF THERMODYNAMICS - Mukhtar Н.М.; Penkov Ф.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
In this article, we review Einstein’s work in the field of thermodynamics. Einstein is one of the most famous scientists who have their place in the field of physics. One of the most important innovations was the discovery of the theory of relativity. However, Einstein also conducted research in other areas of physics. One of them is thermodynamics. The main purpose of this article is to give a small description of Einstein’s work in the field of thermodynamics. Comparing the work of scientists and Einstein, who did the same work in the field of thermodynamics, you can see the main differences or similarities between it and it. Einstein laid the groundwork for some new ideas in this area. Currently, the scope of Einstein’s work in the field of thermodynamics is unknown. There are works of scientists who mistakenly call their theories in the field of thermodynamics. However, it is enough that Einstein’s idea of Brownian motion could provide answers to some questions in the field of nanotechnology and serve as the initial basis for many new works.